Penerapan Permainan Robot Arabic dalam Meningkatkan Kemampuan Mengenal Angka Bahasa Arab di Kelompok B RA Al-Ikhlas Minasa Upa - Wahyuni, Wahyuni; T, M. Rusdi; Nur Khalisah Latuconsina,; Andi Halimah,; Sriyanti, A. (NANAEKE: Indonesian Journal of Early Childhood Education, 2025)
This research aims to: a) determine the ability of group B students to recognize Arabic numbers who learn without using the Arabic robot game at RA Al-Ikhlas Minasa Upa; b) Knowing the ability of group B students to recognize Arabic numbers who learn by implementing the Arabic robot game at RA Al-Ikhlas Minasa Upa; c) Knowing the difference in the ability to recognize Arabic numbers between group B students who learn without using the Arabic robot game and those who learn by implementing the difference whitout using the Arabic robot game and those who learn by implementing the Arabic robot game at RA Al-Ikhlas Minasa Upa. The type of research used is experimental research with quasi-experimental research. The population in this study was all group B at RA Al-Ikhlas Minas Upa which consisted of 6 classes. In this study, the samples were groups B2 (experiment) and B3 (control). The data collection method is tests and documentation with the instrument used, namely the test rubric sheet. The research uses prerequisite tests in the form of normality tests and homogeneity tests as well as hypothesis tests in the form of the Mann Whitney test. The results of this research show that: a) The ability of group B students to recognize Arabic numbers who learned without using the Arabic robot game at RA Al-Ikhlas Minasa Upa has increased; b) The ability of students to recognize Arabic numbers who learn by applying the Arabic robot game at RA Al-Ikhlas Minasa Upa has increased more than children who learn without using the Arabic robot game; c) There is a difference in the ability to recognize Arabic numbers between group B students who learn without using the Arabic robot game and those who learn by using the Arabic robot game at RA Al-Ikhlas Minasa Upa.